2016
DOI: 10.1108/so-08-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and management of risks associated with outsourcing in China

Abstract: Purpose The purpose of this paper is to analyse the risks associated with outsourcing production to emerging countries with lower labour costs, namely China, and study actions and plans used to reduce the influence of factors/drivers that induce these risks. Design/methodology/approach This research uses a multiple case-study methodology, involving seven Canadian manufacturing firms that have chosen an outsourcing strategy in China. It is based on a particular approach of classifying factors/drivers that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…China has increasingly become one of the most attractive destinations for global sourcing by providing various benefits such as cost reduction, capability access, ability to focus on core competencies, and enhanced flexibility. However, despite the benefits China sourcing is not free of problems and risks (El Fadil and St-Pierre, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…China has increasingly become one of the most attractive destinations for global sourcing by providing various benefits such as cost reduction, capability access, ability to focus on core competencies, and enhanced flexibility. However, despite the benefits China sourcing is not free of problems and risks (El Fadil and St-Pierre, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sim (2020) reported that studies of the cost benefits of human resource outsourcing had yielded an equal amount of significant and insignificant results. However, El Fadil and St-Pierre (2016) assert that outsourcing does not lead to low cost.…”
Section: Theoretical Foundation a Model Of The Research And Hypotheses Developmentmentioning
confidence: 99%